2019
DOI: 10.3233/jad-181184
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Apolipoprotein E4 Expression Results in Proteome-Wide Alterations and Compromises Bioenergetic Capacity by Disrupting Mitochondrial Function

Abstract: Apolipoprotein (apo) E4, the major genetic risk factor for Alzheimer’s disease (AD), alters mitochondrial function and metabolism early in AD pathogenesis. When injured or stressed, neurons increase apoE synthesis. Because of its structural difference from apoE3, apoE4 undergoes neuron-specific proteolysis, generating fragments that enter the cytosol, interact with mitochondria, and cause neurotoxicity. However, apoE4’s effect on mitochondrial respiration and metabolism is not understood in detail. Here we use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 125 publications
4
61
0
Order By: Relevance
“…In our case, functional recovery would be obtained by expressing an E2F4 form unable to become Thr phosphorylated, thus counteracting the pathological environment that favors E2F4 phosphorylation. In this way, neuronal E2F4DN expression could efficiently target the complex etiology of AD (15)(16)(17)(18), thus becoming a promising molecule for a successful therapy against this devastating disease.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, functional recovery would be obtained by expressing an E2F4 form unable to become Thr phosphorylated, thus counteracting the pathological environment that favors E2F4 phosphorylation. In this way, neuronal E2F4DN expression could efficiently target the complex etiology of AD (15)(16)(17)(18), thus becoming a promising molecule for a successful therapy against this devastating disease.…”
Section: Discussionmentioning
confidence: 99%
“…An intriguing explanation for GABAergic interneuron selective vulnerability to apoE4, then, is that they have unique demands for high energy production which, in turn, makes them vulnerable to any perturbation of mitochondrial function [189, 190]. A recent study reports that apoE4-expressing neuronal cells have 50% less reserve capacity to generate ATP than apoE3-expressing neuronal cells as well as widespread changes in mitochondrial protein production and translocation, which makes apoE4-expressing neuronal cells more vulnerable to metabolic stress [191]. Building off these data, a testable hypothesis is that apoE4-induced mitochondrial dysfunction is especially damaging to GABAergic interneurons because of their especially high demands for metabolic energy.…”
Section: Introductionmentioning
confidence: 99%
“…These results are congruent with other studies of APOE4 and AD. For example, a recent study by our group demonstrated that E4 astrocytes have increased lactate production 53 , and neurons expressing E4 exhibit increased reliance on glycolysis for ATP production with apparent deficits in mitochondrial respiration 54 . Interestingly, another study showed that fibroblasts from AD patients show a ‘Warburg-type’ (aerobic glycolysis) shift from oxidative phosphorylation to glycolysis with increased lactate production 55 .…”
Section: Discussionmentioning
confidence: 99%